Josephine Bacon: Exotic Fruits and Vegetables A–Z - Jaine, Tom (Petits Propos Culinaires, 2005)
Josephine Bacon: Exotic Fruits and Vegetables A–Z: UPSO, 2004: ISBN 1843750384: 236 pp., paperback, £11.99. Copies available from the publishers at 5 Stirling Road, Castleham Business Park, St Leonards on Sea TN38 9NW, or via websites at www.josephinebacon.co.uk or www.americanization.com.